Gephyrocapsa huxleyi (Emiliania huxleyi) as a model system for coccolithophore biology - Wheeler, Glen L (Journal of phycology, 2023)
© 2023 The Authors. Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.